Perancangan Sistem Informasi untuk Meningkatkan Kinerja Administrasi Pendataan Rumah Penduduk Miskin - Kasmawati; Baizah, Zahratul; Fadli (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The development of an information system for low-income households aims to improve the efficiency of data management for impoverished homes in Glumpang Tiga District. This system replaces the less effective use of Microsoft Excel by leveraging Microsoft Access 2007 for the database and Microsoft Visual Basic 6.0 for the user interface. The primary objective of the system is to simplify data input, information retrieval, and report generation. The development process begins with a feasibility analysis, followed by the design of the database and user interface. A login form is implemented to restrict access, ensuring that only authorized personnel can manage the data. The data input feature enables officers to record information related to households, residents, and family members, with clearly defined category settings. The reports generated are directly applicable for analyzing low-income household data. This system is expected to provide a structured and easily accessible solution for data management, assisting authorities in more accurate planning for development and community empowerment programs.